Identifikasi Situs Candi Bukit Carang, Karanganyar Menggunakan Metode Geolistrik Tahanan Jenis Konfigurasi Dipol-Dipol - Diah Sri Jayanti; Darsono D; Budi Legowo (Department of Physics, Sebelas Maret University, 2016)
Identification of temple sites have been performed on the Bukit Carang region atAnggrasmanis, Jenawi, Karanganyar, Central Javausing the geoelectricity resistivitymeasurement with a dipoles configuration method. This method can determine buried sites around the site groundwork. Software Surfer ver 8.0 and Res2dinv ver 3.30b are used to analyze the mapping data and the sounding data, respectively. This research foundelevenanomalies structured andesite’s rock with resistivity of935-1511 Ωmwhich is considered as temple sites.